Biomass and carbon stocks in 12-year-old Acacia mangium managed at variable density and pruning regimes in central Kerala, India - Rocha, D.; Kunhamu, T.K.; Santhoshkumar, A.V.; Jamaludheen, V.; Raj, Asha K. (Indian Journal of Agroforestry, 2020)
Fast growing-short rotation exotic trees are known for their high biomass production and carbon sequestration potential in the tropics. They are however assumed to act as water and nutrient pumps and probably drain the soil resources through frequent harvest related exports from the site. Despite such concerns, they augment ecosystem services especially through faster rates of elemental carbon accretion in the biomass and soil there by contributing to climate change mitigation. Stand density management may regulate the productivity functions in such systems. A field study was carried out on biomass production (destructive sampling) in a 12-year-old fast growing Acacia mangium stand that was managed in factorial RCBD at planting densities viz. 625, 1250, 2500, 5000 trees ha–1 and two pruning levels (50% pruning and no pruning) in three replications at Kerala, India. The total biomass production (aboveground+belowground) increased with increasing planting density with average production ranging from 158.14 Mg ha–1 (625 trees ha–1) to 332.97 (5000 trees ha–1). Total Carbon stocks also followed same trend that ranged from 66.58 Mg ha-1 (625 trees ha–1) to 152.16 Mg ha–1 (5000 trees ha–1). Variation was abounding in biomass and carbon allocation patterns with stemwood and coarse representing the highest contribution. Results indicate that variable planting density could regulate the biomass production and allocation patterns there by influencing the overall productivity of the Acacia mangium based ecosystem.